The effect of Kappaphycus alvarezii fraction on plasma glucose, Advanced Glycation End-products formation, and renal RAGE gene expression. Issue 1 (January 2021) - Yulianti, Evy; Sunarti,; Wahyuningsih, Mae Sri Hartati
Abstract: Background: Kappaphycus alvarezii (Doty) Doty ex P.C.Silva is a red algae with antioxidant and antiglycation activities. Algae still have not been widely used for treating diabetes, especially to prevent complications. The purpose of this study was to examine the effect of active fractions from Kappaphycus alvarezii on plasma glucose level, glycation process and renal RAGE gene expression. Methods: This study used bioassay-guided fractionation, consisting of three stages: extraction, partition, and fractionation. These processes were monitored with Thin Layer Chromatography and the BSA-Glucose method to select the best extract with antiglycation activity (calculated as the percentage of inhibition and IC50 ). The selected active fraction from four fractions was further used for in vivo study, which was conducted with hyperglycemic Wistar male rats. Plasma glucose level was measured using GOD-PAP methods, while plasma glycated albumin (GA) and Nε- (carboxymethyl) lysine (CML) levels were measured using ELISA. Renal RAGE gene expression was analyzed using qPCR. Results: Fraction II was selected as the active fraction of Kappaphycus alvarezii showing antiglycation activity with the highest percentage of inhibition and the lowest IC50. This fraction significantly reduced plasma GA and CML levels, but it did not significantly reduce plasma glucose level. Furthermore, renal RAGE gene expression was lower in the diabetic rat group treated with this active fraction compared to the untreated group. Conclusions: This study successfully identified an active fraction of Kappaphycus alvarezii with antiglycation activity to reduce plasma GA and CML levels as well as renal RAGE gene expression. Therefore, this fraction could be developed as a potential candidate for treating diabetes. Abstract : Kappaphycus alvarezii, Diabetics, Glycation, IC50, Glucose, Glycated albumin, Nε- (carboxymethyl) lysine, RAGE.